2011
DOI: 10.1007/s12291-011-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibronectin Concentration in Obese/Overweight Pregnant Women: A Possible Risk Factor for Preeclampsia

Abstract: Plasma fibronectin (FN) levels in obese/overweight and non-obese pregnant women were evaluated as a possible risk factor for preeclampsia. A total of one hundred and sixty three pregnant women attending antenatal clinic at University of Calabar Teaching Hospital participated in the study and sixty non-pregnant women served as control. About 77 (47.24%) of the pregnant women were followed up for any subsequent development of preeclampsia during the pregnancy. Fibronectin levels in plasma were measured by ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Plasma FN as an initial factor plays a crucial role in wound healing because it binds to fibrinogen and induces cell migration mostly via its interaction with integrin α 5 β 1 (Lenselink, ). Our analysis of human serum showed a pFN concentration of approximately 315 μg/ml in a donor pool, which is in line with reported concentrations of 220–380 μg/ml for healthy donors (Ekaidem, Bolarin, Udoh, Etuk, & Udiong, ; Fucikova, et al, ; Telci et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Plasma FN as an initial factor plays a crucial role in wound healing because it binds to fibrinogen and induces cell migration mostly via its interaction with integrin α 5 β 1 (Lenselink, ). Our analysis of human serum showed a pFN concentration of approximately 315 μg/ml in a donor pool, which is in line with reported concentrations of 220–380 μg/ml for healthy donors (Ekaidem, Bolarin, Udoh, Etuk, & Udiong, ; Fucikova, et al, ; Telci et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the adipose tissue gene expression of FINC was significantly downregulated in those who successfully maintained their weight after the CR intervention and the following weight maintenance phase [40]. Studies have suggested that increased FINC plasma levels are related to DM, cardiovascular disease, kidney disease, and pre-eclampsia [41,42,43,44,45,46]; therefore, the significant decrease in FINC plasma levels throughout the interventions in both groups suggests that CRPS is beneficial in metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 What is more, FN1 is regarded as a risk factor of EOPET especially among the fubsy women. 41 In consequence, FN1 may be also considered as a biomarker of EOPET.…”
Section: Discussionmentioning
confidence: 99%